The diversity of chronic hepatitis B virus infections within blood donors in England and North Wales 2005 through 2010. Issue 10 (7th December 2012) - Rosenberg, Gillian K.; Lattimore, Sam; Brailsford, Susan R.; Hewitt, Patricia E.; Tettmar, Kate I.; Kitchen, Alan D.; Ijaz, Samreen; Tedder, Richard S.
Abstract : Background: In 2010 hepatitis B virus (HBV) was the most frequently detected infection in UK blood donation screening, typically found in first‐time, male, chronically infected donors born abroad. To date there has been no comprehensive characterization of the virologic profile of these infections. Study Design and Methods: Epidemiologic and serologic data were collected retrospectively for 344 chronically HBV‐infected blood donors identified from July 2005 to June 2010. Additional laboratory testing was carried out to determine the HBV genotype, viral load, and prevalence of clinically significant mutations and to detect hepatitis delta virus (HDV) coinfection. Results: Five HBV genotypes (A‐E) were found, Genotypes D (45%), A (20%), and E (20%) were the most prevalent. A strong association was seen between genotype and donor ethnicity (p < 0.001) and between genotype and place of residence (p = 0.006). Clinically significant mutations were observed across hepatitis B surface antigen (17%), basal core promoter (25%) and precore (78%) regions. An antiviral resistance profile was identified in one donor. Evidence of HDV coinfection was found in 2% of donors. Conclusion: The data show the diversity of HBV in asymptomatic chronic infections detected in blood donors in England and North Wales and demonstrates the presence of mutations which may impact on disease. The global nature of these infections and the inability to identify chronically infected donors before donation highlights the importance of using screening assays capable of detecting a broad range of genotypes and mutations. Furthermore, the integration of the virologic and demographic data allows us to more accurately construct a profile of our chronically HBV‐infected blood donors.